(untitled) (Práxis Educativa, 2019)
This research aimed at identifying and analyzing tutors’ pedagogical practices, in Distance Learning, in order to encourage the use of cognitive, behavioral and self-regulatory learning strategies by the students. For data collection, an online survey was applied, composed by 7 questions which asked the tutor about his/her pedagogical practices in face of several situations in the school context. Twenty-six tutors took part in the survey and the answers were evaluated according to Bardin’s (2004) Content Analysis assumptions. When the tutors’ pedagogical practices were analyzed, it was verified they indicated that behavioral strategies were encouraged more often. Generally, it was observed that the tutors’ pedagogical practices were not aimed at promoting the use of learning strategies. The results of this research point to the need for new intervention studies that aim to teach learning strategies to distance learning tutors. Keywords: Tutor. Distance learning. Learning strategies.